1993
DOI: 10.1002/jlb.54.6.590
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexanoic acid (22:6, n-3) but not eicosapentaenoic acid (20:5, n-3) can induce neutrophil-mediated injury of cultured endothelial cells: involvement of neutrophil elastase

Abstract: Previously published work has indicated that polyunsaturated fatty acids (PUFA) may enhance neutrophil-mediated damage to host tissues. We have found that endothelial detachment was significantly increased by neutrophils pretreated with docosahexaenoic (22:6, n-3) and arachidonic (20:4, n-6) acids at 10-40 microM but not by eicosapentaenoic acid (20:5, n-3). Endothelial cell lysis as measured by 51Cr release was unaffected. The extent of detachment was dependent on both fatty acid and neutrophil pretreatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
4
18
0
2
Order By: Relevance
“…Consistent with this report was the finding that enrichment of corn oil in the diet resulted in a dramatic reduction in blood and liver vitamin E content [7]. Another important observation concerning n-6 PUFA was from Bates et al [12] who showed that AA pretreatment of neutrophils decreased endothelial integrity through detachment involving neutrophil elastase.…”
Section: Introductionsupporting
confidence: 70%
“…Consistent with this report was the finding that enrichment of corn oil in the diet resulted in a dramatic reduction in blood and liver vitamin E content [7]. Another important observation concerning n-6 PUFA was from Bates et al [12] who showed that AA pretreatment of neutrophils decreased endothelial integrity through detachment involving neutrophil elastase.…”
Section: Introductionsupporting
confidence: 70%
“…A number of studies have demonstrated that AA has a major influence on leukocyte responses. AA stimulates the production of oxygen radicals (12, [22][23][24][25][26], release of granule enzymes, increases adherence and damage to the endothelium (26)(27)(28), and inhibits cell migration (13).…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the ability of the delipidated albumin to "extract" the fatty acids from the plasma membrane and perhaps the cell interior. Such a rapid termination of the effects of AA suggests that the fatty acid may be located in the outer leaflet for biological activity or that there is a very rapid reverse transport/diffusion from the cell interior to the outer leaflet and that the native and NEFA, not a metabolite, is responsible for the biological action [10,12].…”
Section: Do Fatty Acids Need To Enter the Cells To Act And What Mechamentioning
confidence: 99%